Attitudes Towards Older Australian Workers. (15th June 2015) - Helmes, Edward
Abstract : Many employers in Australia are experiencing ageing workforces. Yet ageist attitudes and discrimination can impede effective management of older workers. Here we explore the attitudes of a mixed sample of university undergraduates and community members towards older workers. A total of 64 males and 89 females completed questionnaires assessing attitudes towards older workers and general knowledge of older adults. The association between these factors and respondents' age, gender, education, employment status and hours worked per week was examined. As predicted, the sample's attitudes towards older workers were generally positive among those who were working, but hypotheses relating to associations between knowledge of ageing, age, education and hours worked per week were largely not supported. The failure of variables hypothesised to be related to attitudes is discussed.